VD_FINDINFO Arrêt / 2014 / 296 vom 25. März 2014 - VD Tribunal cantonal (2014)
REJET DE LA DEMANDE, CURATELLE DE GESTION, CURATELLE DE REPRÉSENTATION | 390 al. 1 ch. 1 CC, 394 al. 1 CC, 395 al. 1 CC, 395 al. 3 CC, 450 CC